"Accepting "˜Eternity’ of Antiretroviral Drugs": A Pillar in Improving Adherence to Antiretroviral Drugs among a Selected Population of HIV Positive Patients in a Semi-Urban Region in Kenya - A Qualitative Analytic Study - Ochieng, Martin; Kikuvi, Gideon; Mokaya, Daniel (Global Journal of Health Sciences, 2023)
Purpose: The objective of this research was to ascertain perspectives on suboptimal adherence and ways to improve optimal adherence to antiretroviral drugs (ARVs) among Human Immunodeficiency Virus (HIV) positive patients attending selected HIV Care Centres in Kibwezi West Sub-county, Makueni County, Kenya. Methodology: Six Focused Group Discussions (FGD) homogeneously stratified by age and gender and four Key Informant Interviews (KII) were conducted. Each FGD consisted of 8 study participants recruited by purposive sampling technique. Findings: Focus group discussions identified fear, stigma, defiance, ignorance on reasons for medication, not believing in oneself, participating in activities that hinder adherence such as drinking alcohol, retrogressive religious beliefs, lack of self-love and denial as the main causes of sub optimal adherence to ARVs. However the discussions also identified one-on-one educational counselling sessions, seeking advice, group education with similar infected people, adherence counselling support by health workers, acceptance of one's status, social and family support as means to improve adherence to ARVs. It also identified knowing one's status, acceptance, personal discipline on adherence and reminders such as clock alarms or a trusted person as means to improve adherence to ARVs. However, the discussions revealed gender and age differences, attributed to different life's challenges and perspectives in the different cohorts thus interventions should be targeted rather than lump sum. Key informant interviews identified ignorance, stigma, busy work schedule and lack of social support as patient level factors that would hinder adherence to ARVs. They also noted long waiting time, distance, poor attitude by health service providers and drug stock outs contributing to poor adherence to ARVs at the facility level. However, they identified community dispensing, support groups, health talks with mentors, psychosocial support, drug availability, outreach, encouraging disclosure, distribution of patients to nearest satellite clinics and directly observed therapy (DOT) by a trusted relative as ways to improve adherence to ARVs. Unique Contribution to Theory, Practice and Policy: interventions need to be tailored to the specific population and individual needs; thus, adopting better and informed strategies. The study adds to the pool of knowledge that factors affecting adherence are dependent on populations under investigation due to varied socio-demographic, socio-cultural and socio-economic factors locally, regionally and globally. The findings of the study will inform the local county government of Makueni and Kibwezi West Sub-county administrators in formulating local economic and health policies and by-laws that would aid in improving optimal adherence to ARVs.